2020
DOI: 10.26434/chemrxiv.12275603.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PM2.5 and Ozone Air Pollution Levels Have Not Dropped Consistently Across the US Following Societal Covid Response

Abstract: <p>Analysis of a large national dataset of fine particulate matter (PM2.5) and ozone air pollution from the US Environmental Protection Agency indicate opposing differences in average concentrations during the covid response period, relative to expected levels. These are the two most important pollutants in terms of public health impacts and regulatory non-attainment in the US. Post-covid response, average PM2.5 levels are slightly higher (~6%) than expected; average ozone levels are slightly lower (~5%)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
12
2
Order By: Relevance
“…In the USA one study using EPA data showed a mean decrease of 30% of NO2 in urban areas of Seattle, Los Angeles and New York during the lockdown. The study did not show any consistent change in O3 levels (Bekbulat et al, 2020).…”
contrasting
confidence: 56%
“…In the USA one study using EPA data showed a mean decrease of 30% of NO2 in urban areas of Seattle, Los Angeles and New York during the lockdown. The study did not show any consistent change in O3 levels (Bekbulat et al, 2020).…”
contrasting
confidence: 56%
“…Satellite NO 2 data suggested that Western Europe and major Northeastern US cities experienced 20–38% NO 2 decreases in 2020 relative to the same period in 2019 although Iran, a region strongly affected by COVID-19, did not show clear evidence of lower NO 2 concentrations ( Bauwens et al, 2020 ). In the US, preliminary results of an ongoing study utilizing daily PM 2.5 and O 3 data obtained from US Environmental Protection Agency indicate that PM 2.5 levels were about 10% higher than expected while O 3 levels were about 7% lower than expected during the post-SHO period compared to the same period in historical years ( Bekbulat et al, 2020 ). Additionally, preliminary analysis of this study shows that NO 2 levels in Seattle were 20% lower than expected ( Bekbulat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the US, preliminary results of an ongoing study utilizing daily PM 2.5 and O 3 data obtained from US Environmental Protection Agency indicate that PM 2.5 levels were about 10% higher than expected while O 3 levels were about 7% lower than expected during the post-SHO period compared to the same period in historical years ( Bekbulat et al, 2020 ). Additionally, preliminary analysis of this study shows that NO 2 levels in Seattle were 20% lower than expected ( Bekbulat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brodeur and NO2 in New York City (NYC), when using a linear time series model to compare pollutant levels following the NYC shutdown to the same weeks in 2015 -2019. One consideration in the interpretation of estimates by Bekbulat at al. (2020) is that they analyzed data from across the U.S., where restrictions and compliance with federal directives was very heterogeneous.…”
Section: Literature Reviewmentioning
confidence: 99%